2004
DOI: 10.1007/s00216-004-2521-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioimprinted QCM sensors for virus detection?screening of plant sap

Abstract: Surface imprinting techniques on polymer-coated quartz-crystal microbalances (QCM) have been used to detect tobacco mosaic viruses (TMV) in aqueous media. Molecularly imprinted polymers (MIP), tailor-made by self organisation of monomers around a template (TMV), were generated directly on the gold electrodes. Imprinted trenches on the polymer surface mimicking the shape and surface functionality of the virus serve as recognition sites for re-adsorption after washing out of the template. The sensors are applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
1
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(82 citation statements)
references
References 22 publications
0
72
1
6
Order By: Relevance
“…Since QCM has proven to be successful in detection of plant viruses, including Cymbidium mosaic virus (CyMV), TMV and Turnip yellow mosaic virus (TYMV), were detected using QCM (Dickert et al, 2004;Eun et al, 2002;Zan et al, 2012).…”
Section: Quartz Crystal Microbalance Immunosensors (Qcmi)mentioning
confidence: 99%
“…Since QCM has proven to be successful in detection of plant viruses, including Cymbidium mosaic virus (CyMV), TMV and Turnip yellow mosaic virus (TYMV), were detected using QCM (Dickert et al, 2004;Eun et al, 2002;Zan et al, 2012).…”
Section: Quartz Crystal Microbalance Immunosensors (Qcmi)mentioning
confidence: 99%
“…[2,3] Vorteile der MIPs sind ihre mechanische und chemische Stabilität, ihre niedrigen Kosten und ihre einfache Herstellung. [4] Das Prägen von Oberflächen wurde bereits angewendet, um künstliche Rezeptoren auf dünnen Polymerfilmen für die Erkennung von Proteinen, [5] PflanzenViren [6] und Hefezellen [7] herzustellen. Hier soll die Eignung des Oberflächenprägens für die Erkennung von Säugetier-zellen gezeigt werden.…”
unclassified
“…Unser Die Kohlenhydrat-Antigene des AB0-Systems sind die häufigsten Antigene auf der Glycocalix-Oberfläche der Erythrozyten: [10] Die Zahl der AB0-Antigene auf der Oberfläche eines einzelnen Erythrozyten beträgt im Durchschnitt 10 5 -10 6 . [11] Ihre Dichte ist damit bis zu 100-mal höher als die der Epitope anderer Antigene.…”
unclassified
“…57! O transporte viral célula à célula é um processo ativo provido por proteínas de movimento viral (MP) que geralmente se associam com fatores do hospedeiro e outros componentes virais possibilitando o transporte célula à célula e sistêmico (Aparicio et al, 2010;Dickert et al, 2004;Navarro et al, 2006;). …”
Section: B"unclassified
“…Cell-to-cell and systemic transports of viruses are provided via viral movement proteins (MPs) that generally associate themselves to host factors and other viral components (Aparicio et al, 2010;Dickert et al, 2004;Wolf et al, 1989). Genetic and molecular biology studies have demonstrated that those proteins, denoted movement proteins (MPs), interact with the plasmodesma (PD) enhancing its exclusion limit and allow the virus passage (Wolf et al, 1989).…”
Section: Introductionmentioning
confidence: 99%